2018
DOI: 10.25135/rnp.23.17.07.126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olea europaea L. Leaf Metabolites on the Tilapia (Oreochromis niloticus) and Three Stored Pests, Sitophilus granarius, Tribolium confusum and Acanthoscelides obtectus

Abstract: Olea europea L. emerged as a good source of traditional medicine for the treatment of various ailments of various countries of the world, in particular Mediterranean countries. In this study, oleuropein (1), oleanolic acid (2), maslinic acid (3), a mixture of erythrodiol and uvaol (4 and 5) isolated from the leaves of olive were added at two concentrations (1g/100g feed and 4g/100 g feed) into fish feed. Oreochromis niloticus (Nile tilapia) were fed twice a day with the feed during 96 hours. The levels of alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…pinnata were widely used as fish feeds, as it promotes growth of fingerlings and adults [ 68 , 69 ]. Toxic materials are present in all plant materials; however, the effects of toxic material on the environment differs according to the plant species [ 70 ]. As an example, the Olea europea leaf contains maslinic acid, which has lower toxic effects on the environment compared to that of chemical insecticides [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pinnata were widely used as fish feeds, as it promotes growth of fingerlings and adults [ 68 , 69 ]. Toxic materials are present in all plant materials; however, the effects of toxic material on the environment differs according to the plant species [ 70 ]. As an example, the Olea europea leaf contains maslinic acid, which has lower toxic effects on the environment compared to that of chemical insecticides [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toxic materials are present in all plant materials; however, the effects of toxic material on the environment differs according to the plant species [ 70 ]. As an example, the Olea europea leaf contains maslinic acid, which has lower toxic effects on the environment compared to that of chemical insecticides [ 70 ]. Hence, depending on the plant species, natural insecticides from plants may possess lesser effects on the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds of botanical origin which coevolved as defense mechanisms against herbivores and pathogens have been proposed as a promising strategy but few are commercially produced [9,10]. Numerous investigations of their protective power against storage pests is taking place, and insecticidal and repellent properties of plant powders [11][12][13], plant extracts [14][15][16], and essential oils are tested [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Toxic effects of plant extracts, essential oils and various secondary metabolite products have been reported in different researches (Kesdek et al, 2015;Usanmaz et al, 2016;Kısa et al, 2018). The present study showed that under in vivo (between 2.22 and 100%) and in vitro (between 8.88 and 100%) conditions, the ethanol extracts of six Satureja plant species had the strong insecticidal activity based on the mortality of all the tested (1 st , 2 nd , 3 rd and 4 th ) instars larvae and adults of L. decemlineata.…”
Section: Insecticidal Activity Extractsmentioning
confidence: 99%